Survivin Promotes Piperlongumine Resistance in Ovarian Cancer - Nan, Xing-Wei; Gong, Li-Hua; Chen, Xu; Zhou, Hai-Hong; Ye, Piao-Piao; Yang, Yang; Xing, Zi-Hao; Wei, Meng-Ning; Li, Yao; Wang, Sheng-Te; Liu, Kun; Shi, Zhi; et al. (Frontiers in Oncology, 2019)
Ovarian cancer is one of the most lethal malignancies, while targeting apoptosis is critical for improving ovarian cancer patients' lives. Survivin is regarded as the most robust anti-apoptosis proteins, and its overexpression in ovarian cancer is associated with apoptosis resistance and poor survival. Piperlongumine (PL) is a biologically active alkaloid/amide from peppers and exhibits a broad spectrum of antitumor effects. Here, we demonstrate that PL rapidly reduces survivin levels in ovarian cancer cells via reactive oxygen species (ROS)-mediated proteasome-dependent pathway in vitro, while concurrently exerting a significant inhibitory effect on the proliferation of ovarian cancer cells. Overexpression of survivin raises the survival rate of ovarian cancer cells to PL. Moreover, PL inhibits ovarian cancer cells xenograft tumor growth and downregulates survivin in vivo. Our findings reveal a previously unrecognized mechanism of PL in suppressing survivin expression as well as survivin promotes piperlongumine resistance in ovarian cancer and suggest that ROS-mediated proteasome-dependent pathway can be exploited to overcome apoptosis resistance triggered by aberrant expression of survivin.